Merriam-Webster's school dictionary. - Merriam-Webster, Inc. (USA : Merriam-Webster, Incorporated, 2004)
A study aid for students, this dictionary provides up-to-date content, word guidance, and comprehensive coverage of meanings, spellings, and pronunciations.
Using the dictionary -- Abbreviations used in this dictionary -- Pronunciation symbols -- A dictionary of the English language -- Abbreviations and symbols for chemical elements -- Biographical, biblical, and mythologoical names -- Geographical names -- Signs and symbols -- A handbook of style.
"For students age 14 & up, grades 9-11"--Page 4 of cover.
Keywords: English language -- Dictionaries, Juvenile